Mind Map Research of 5 Years: Financial Modeling and Pro Forma Analysis - Asri Solihat (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
Abstract- The complexity of the business and financial world in the 4.0 industrial revolution era, making decision making needs to pay attention to financial modeling and pro forma analysis. This research uses descriptive method by reviewing 15 articles about financial modeling and pro forma analysis in the last 5 years. The results of the analysis for 5 years have not shown the relationship between profitability and risky cash flow and its implications for financial modeling and its effect on proforma analysis. Related to further research, designing a model in the figure can be a relevant reference to the development of financial management science of the industrial revolution era 4.0. Abstrak– Kompleksnya dunia bisnis dan keuangan pada era revolusi industry 4.0, membuat pengambilan keputusan perlu memperhatikan financial modeling dan pro forma analysis. Penelitian ini menggunakan metode deskriptif dengan mengkaji 15 artikel tentang financial modeling dan pro forma analysis pada kurun waktu 5 tahun terakhir. Hasil analisis selama 5 tahun belum mengungkapkan hubungan antara profitability dengan cashflow at risk serta implikasinya pada financial modeling dan dampaknya pada proforma analysis. Sehingga dalam penelitian berikutnya, rancangan model pada gambar dapat menjadi rujukan yang relevan dengan perkembangan ilmu manajemen keuangan era revolusi industry 4.0.